2008
DOI: 10.1107/s0108270108012067
|View full text |Cite
|
Sign up to set email alerts
|

Assembling an isomer grid: the isomorphous 4-, 3- and 2-fluoro-N′-(4-pyridyl)benzamides

Abstract: The three title isomers, 4‐, (I), 3‐, (II), and 2‐fluoro‐N′‐(4‐pyridyl)benzamide, (III), all C12H9FN2O, crystallize in the P21/c space group (No. 14) with similar unit‐cell parameters and are isomorphous and isostructural at the primary hydrogen‐bonding level. An intramolecular C—H...O=C interaction is present in all three isomers [C...O = 2.8681 (17)–2.884 (2) Å and C—H...O117–118°], with an additional N—H...F [N...F = 2.7544 (15) Å] interaction in (III). Intermolecular amide–pyridine N—H...N hydrogen bonds l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(64 citation statements)
references
References 11 publications
8
56
0
Order By: Relevance
“…Single crystals of the Fxx isomers including the three Fxp compounds (Donnelly et al, 2008) were obtained by slow evaporation of solutions at 277 or 294 K and typically from ethyl acetate, while Fmo was grown from CDCl 3 . The only Fxx isomer that proved difficult to crystallize as diffraction quality crystals was Fom: decent quality crystals were only obtained after a series of crystal growth experiments from mixtures of methanol and diethyl ether.…”
Section: Single-crystal Growth and X-ray Crystallography Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Single crystals of the Fxx isomers including the three Fxp compounds (Donnelly et al, 2008) were obtained by slow evaporation of solutions at 277 or 294 K and typically from ethyl acetate, while Fmo was grown from CDCl 3 . The only Fxx isomer that proved difficult to crystallize as diffraction quality crystals was Fom: decent quality crystals were only obtained after a series of crystal growth experiments from mixtures of methanol and diethyl ether.…”
Section: Single-crystal Growth and X-ray Crystallography Methodsmentioning
confidence: 99%
“…All nine Fxx isomers were synthesized using standard nucleophilic acyl substitution reactions (Schö tten-Baumann reaction) between the 4-/3-/2-aminopyridines and 4-/3-/2fluorobenzoyl chlorides at 294 K. The general procedure is as described for the Fxp triad of compounds (Donnelly et al, 2008): an alternative route is reported by Lu et al (2003). The Fxm isomers were prepared by the condensation reaction of 3aminopyridine (3-AP) with 4-/3-/2-fluorobenzoyl chlorides in CH 2 Cl 2 in the presence of 1 equiv of triethylamine (Et 3 N).…”
Section: General Description Of the Fxx Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…Subtle differences at the molecular level do not impact on the overall molecular aggregation (isomorphous series) and differences between the crystal structures are noted at the secondary level. [40][41][42][65][66][67][68][69][70][71][72] Why is there such a considerable overlap between Clxx, Brxx but not with Fxx or Mxx?…”
Section: Summary Of the CLXX Solid-state Structural Resultsmentioning
confidence: 99%